2018
DOI: 10.18203/2394-6040.ijcmph20183562
|View full text |Cite
|
Sign up to set email alerts
|

Detection of biofilm formation by Escherichia coli with its antibiogram profile

Abstract: Background: In urinary tract infections, an important role is played by bacterial biofilms which are responsible for persistence infections together with the antimicrobial resistance. Higher resistance can be seen in biofilm forming uropathogens in comparison with free-floating bacteria. So, the present study was performed with a goal to find the prevalence of biofilm formation and also the antimicrobial resistant pattern of uropathogens.Methods: A descriptive method was conducted at Modern Technical College, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
3
9
0
Order By: Relevance
“…In the MTPA, the number of isolates showing biofilm formation was 38 (38%) (30 strong and 8 moderate) and no weak biofilm producers were detected. A previous study showed from the 50 clinical isolates, 32 were biofilm producers (3 strong and 29 moderate) and 18 were weak/non-biofilm [17]. In another study, of the 50 isolates, 25 each were environmental and clinical.…”
Section: Discussionmentioning
confidence: 88%
“…In the MTPA, the number of isolates showing biofilm formation was 38 (38%) (30 strong and 8 moderate) and no weak biofilm producers were detected. A previous study showed from the 50 clinical isolates, 32 were biofilm producers (3 strong and 29 moderate) and 18 were weak/non-biofilm [17]. In another study, of the 50 isolates, 25 each were environmental and clinical.…”
Section: Discussionmentioning
confidence: 88%
“…3 mg of sample and 300 mg of KBr were grounded by means of a mortar and pestle. A small portion of the mixture was compressed at 10 kg/cm in a hydraulic press, resulting in a transparent pellet that was inserted into the sample holder and subjected to scanning in the range of 4000 to 500 cm -1 [5,24].…”
Section: Fourier Transform Infrared Spectroscopy (Ft-ir) Studymentioning
confidence: 99%
“…4 shows the FT-IR spectra of pure PT, the physical mixture of PT with excipients, pure LN, the physical mixture of PT and LN, and the physical mixture of the optimum PT-ODF with LN (S1 formula). The main peaks of PT are at 1411.06 cm -1 , 1554.46 cm -1 , 2937.06 cm -1 , 3350.30 cm -1 , and 3864.50 cm -1 owing to its functional groups (C=C, C=O, C-H, O-H, and N-H), respectively [5,46]. The major peaks of PT were detected in the physical mixture of PT with excipients, indicating the absence of incompatibility.…”
Section: Sem Of the Optimum Pt-odfmentioning
confidence: 99%
See 1 more Smart Citation
“…The biofilm assay was performed following the protocol described by Risal et al (2018) with modifications. Each overnight culture in Tryptone Soy Broth (TSB (HiMedia-India) was diluted to OD 600 = 0.2 (̴ 10 8 CFU/mL), and three 180μL aliquots pippeted into wells of a 96-well microplate.…”
Section: Quantification Of Biofilm Biomassmentioning
confidence: 99%